Modulatory potentials of nitric oxide in obesity-induced endothelial dysfunction - Kwaifa, Ibrahim Kalle; Md Noor, Sabariah (Learning Gate, 2024)
Obesity is caused by a significant increase in adipose tissue due to excessive caloric intake that exceeds energy expenditure. Obesity has emerged as a significant public health issue in both poor resource and economic developed nations, owing to its increased incidence and links to chronic diseases, such osteoarthritis, hypertension, non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases (CVDs). It is believed that uncoupled eNOS, nicotinamide adenine dinucleotide phosphate (NADPH) oxidases, xanthine oxidase, lipoxygenase, cyclooxygenase, microsomal P-450 enzymes, and pro-oxidant heme molecules are responsible for the drastic decrease in NO production and the relative increase in reactive oxygen species (ROS) secretion, which are considered as the molecular mechanisms associated with obesity-induced endothelial dysfunction. Vascular endothelium defines a monolayer of cells, which lies between the vascular smooth muscle cells (VSMCs) and the vessel lumen. It performs a number of protective actions facilitated by the release of nitric oxide (NO), a soluble gas that is generated in endothelial cells by the amino acid L-arginine through the action of endothelial nitric oxide synthase (eNOS). The maintenance of vascular homeostasis is facilitated by various biological actions of NO, such as modulation of vascular dilator tone, control of local cell growth, and protection of the endothelium from the harmful effects of cellular components in blood circulation, while maintaining normal endothelial functions. Decreased peripheral arterial endothelium-dependent dilation (EDD) in response to mechanical (intravascular shear) or chemical (acetylcholine) stimuli suggests that decreased NO bioavailability has been recognised as major molecular mechanisms associated with the progress and development of obesity-induced endothelial dysfunction. In this review, the modulatory effects of NO in obesity-induced endothelial dysfunction will be discussed.